Macrochorobates scalabrinii (Moreno & Mercerat) (Cingulata, dasypodidae) en el mioceno tardío de la provincia de San Juan (Argentina). Implicancias biocronoestratigráficas y paleobiogeográficas - Contreras, Victor (2013)
Macrochorobates scalabrinii is reported and described. The remains come from the upper deposits of the Las Flores Formation (Upper Miocene), outcropping at the Iglesia Valley (Iglesia Department, San Juan Province, Argentina). The detailed study of these osteoderms, including the description of some anatomical and morphological characteristics not mentioned before, provides novel information about the carapace and, in turn, probably allows extending the diagnoses of this taxon. The stratigraphic and chronological distribution would support the importance of Macrochorobates scalabrinii as a biostratigraphic indicator for the Huayquerian Stage/Age. On the other hands, this new discovery confirms the previous hypothesis that point out a biogeographic connection between the Pampean and Northwest regions during the Late Miocene